Students' Perception of Duolingo as an English Learning Tool at Politeknik Negeri Bali Civil Engineering Department - I Gusti Ayu Dewi Paramita; Evin Yudhi Setyono; Ni Nyoman Yuliantini; Ni Ketut Suciani (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This study examined the perception of the Android-based Duolingo application as an English learning resource among students enrolled in the D3 Civil Engineering program at Bali State Polytechnic. Data were collected through surveys and interviews involving thirty-two fourth-semester students, randomly selected from one class to represent the entire population. The study employed a quantitative approach, focusing on gathering detailed information regarding students' perceptions of Duolingo as a supplementary tool for learning English. The results indicated that 3.70% of respondents had a very good perception of Duolingo, 51.85% had a good perception, 33.33% had an adequate perception, and 11.11% had a poor perception. These findings suggest that the majority of D3 Civil Engineering students at Bali State Polytechnic view the Duolingo application positively. Overall, it can be concluded that Duolingo is perceived as an effective and beneficial resource for enhancing English language skills among these students.